The rate and potential of capability development trajectories - Rockart, Scott F.; Dutt, Nilanjana (Strategic Management Journal, 2015)
This paper examines differences in the rate and potential of firms' capability development trajectories. Capability development trajectories are the paths over which firms' capabilities change with experience and other activities. While prior research focused on factors affecting capability development rate (the fraction of the gap between a firm's current and potential capability eliminated with each unit of activity), we argue that capability development trajectories also differ in potential (the maximum capability level a firm could achieve through repeating a given set of activities over time). We develop and estimate a formal model of capability development, showing that larger underwriting projects lead to a lower rate of improvement toward higher potential capabilities, and derive implications for research on industry dynamics and the nature of competitive advantage . Copyright © 2013 John Wiley & Sons, Ltd.